1930
DOI: 10.1002/cber.19300631008
|View full text |Cite
|
Sign up to set email alerts
|

Einwirkung von Quecksilbersalzen auf Aceto‐halogenzucker, IV. Mitteil.: Direkte Darstellung der Alkylbioside der α‐Reihe

Abstract: Z e m p 1 dn , G e r ecs: Einwirkung von [ J a h g . 63 der Lignin-Chemie so selten sind, riihrt daher, daB alle Reagenzien, welche die aliphatische Kette zertrummern, hierdurch gleichzeitig die bis dahin vexatherte 4-Hydroxylgruppe des Benzol-Kerns freilegen und diesen daraufhin angreifen. AuBer den genannten 3 Reaktionen des Kernes -Nitrierung, Bromierung, Mercurierunglassen sich nur einige Reaktionen der aliphatischen H,CO H,CO H,CO Kette, und zwar Umsetzungen sekundarer Hydroxyle, anfiihren, die stochiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1931
1931
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…New methodologies are still being developed with more advanced variations in the mechanistic pathways. Later Zémplén and Gerecs, and subsequently Helferich and Wedermeyer, illustrated the principle of the metal(II) salt‐induced removal of leaving groups . With the general standardization of glycosyl protocols, efforts were made to control the stereochemical outcome of glycosylations.…”
Section: General Aspectsmentioning
confidence: 99%
“…New methodologies are still being developed with more advanced variations in the mechanistic pathways. Later Zémplén and Gerecs, and subsequently Helferich and Wedermeyer, illustrated the principle of the metal(II) salt‐induced removal of leaving groups . With the general standardization of glycosyl protocols, efforts were made to control the stereochemical outcome of glycosylations.…”
Section: General Aspectsmentioning
confidence: 99%
“…Haq aiid Whelan (13) synthesized nigerose, compound 4 of this paper, by a chemically related route. The modification of the Koenigs-Knorr reaction involving the use of mercuric cyanide as condensing agent, introduced by ZemplCn and Gerecs (14) and used by Matsitda (15) for the synthesis of a-D-glucopyranosides, failed (9) to provide 1 but did provide nigerose (15,16). The chemical nature of this approach to the synthesis of a-D-glucopyranosides remains obscure (17) but it has provided syntheses of a number of complex a-D-glucopyrar~osides in low yield (18)(19)(20).…”
mentioning
confidence: 99%
“…Lemieux and Brice (3) have shown that the treatment of pentaacetyl-0-Dglucopyranose (I) with stannic chloride in chlorofornl solutiol~ resulted in a rapid dissociation of the C1 to acetoxy group bond to yield carbonium ions of which the resonance stabilized 1,2-cyclic ion (11) is the predominant type. Treatment of 1,2,3,4-tetraacetyl-/3-D-glucose under these conditions yielded the internal glucoside, triacetyl-D-glucosan (1,5) P (1, 6) (3).…”
Section: Introductionmentioning
confidence: 99%